MOTOR COORDINATION DIFFICULTIES IN CHILDREN WITH LEARNING DISABILITIES - Laganovska, Egija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Nowadays increasing the number of children with learning disabilities in comprehensive schools of Latvia, so it is necessary preventive measures during schooltime. One of the support measures are short movement activity in academic lessons. The aim of article is theoretical analyze the correlations between motor coordination difficulties and the child's academic achievement and find out primary school teachers' views on possible support for children with learning disabilities. Main findings – development of motor coordination in children of primary schools is effective when using short movement breaks in classroom. Research methods: analysis of scientific and methodological literature, a survey of primary school teachers from Riga (88 respondents), data collection and analysis.